Simulation Study of Small-Scale Electricity Generation Plant Utilizing Flue Gas of Solid Garbage Waste Incineration as Energy Source - Simanjuntak, Janter Pangaduan; Pakpahan, Binsar Maruli Tua (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2023)
This study aims to get an overview of the operational parameters of a small-scale electrical generation plant that utilizes thermal energy included in the flue gases of garbage waste incineration. The organic Rankine cycle (ORC) thermodynamic system was performed to evaluate this system. The organic fluid was used as a heat transfer medium instead of water because it has a low boiling point so it does not require a lot of thermal energy to generate small-scale electric power. Hexane was used as the working fluid and Aspen Hysys was used as a tool to perform simulations. The plant is optimized through the operating temperature, working fluid flow rate, and pressure to obtain electrical output power that can be obtained. The simulation results show that flue gas at a temperature range of 300 to 350 0C can produce electric power in the ranges of 7.84 to 128.6 kW at a working pressure ranges of 2.5 to 7.5 bar, and working fluid flow rate of 3.600 to 10.100 kg/h